2023
DOI: 10.1093/jambio/lxad005
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of feather keratin waste to antioxidant and migration-enhancer peptides byBacillus licheniformis8-4

Abstract: Aims Feathers are keratin-rich byproducts of poultry processing but that are often frequently abandoned as garbage and polluting the environment. Therefore, the study focused on the efficient biodegradation, bioactivity, and high-value application of feather keratin. Methods and Results Feather-degrading bacteria were identified and the degradation properties were characterized. DPPH and ABTS radical scavenging assays, cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Feathers, which are the primary byproduct of poultry processing, contain a high proportion of proteins (≥90%), including essential amino acids, making them a valuable source of nutrition. , However, feather keratin, which is a particularly resistant protein, is often disposed of in an unregulated manner, leading to environmental pollution and limiting its potential applications. , Therefore, there is an urgent need to develop environmentally friendly and cost-effective strategies to exploit the high value-added products of feather keratin. Recent studies have shown that hydrolysate peptides derived from feather keratin (FKHPs) possess significant antioxidant activity, as demonstrated by their excellent DPPH and ABTS radical scavenging capacities, as well as their ability to scavenge intracellular ROS. These peptides are also rich in hydrophobic amino acids, which are a characteristic component of uric acid-lowering peptides that have been previously identified, including XOD inhibitory peptides. ,, Thus, we hypothesize that FKHPs may be an ideal source of uric acid-lowering peptides, yet to date, no XOD inhibitory peptides have been identified from FKHPs.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Feathers, which are the primary byproduct of poultry processing, contain a high proportion of proteins (≥90%), including essential amino acids, making them a valuable source of nutrition. , However, feather keratin, which is a particularly resistant protein, is often disposed of in an unregulated manner, leading to environmental pollution and limiting its potential applications. , Therefore, there is an urgent need to develop environmentally friendly and cost-effective strategies to exploit the high value-added products of feather keratin. Recent studies have shown that hydrolysate peptides derived from feather keratin (FKHPs) possess significant antioxidant activity, as demonstrated by their excellent DPPH and ABTS radical scavenging capacities, as well as their ability to scavenge intracellular ROS. These peptides are also rich in hydrophobic amino acids, which are a characteristic component of uric acid-lowering peptides that have been previously identified, including XOD inhibitory peptides. ,, Thus, we hypothesize that FKHPs may be an ideal source of uric acid-lowering peptides, yet to date, no XOD inhibitory peptides have been identified from FKHPs.…”
Section: Introductionmentioning
confidence: 98%
“…Regrettably, these methods often result in energy consumption, environmental pollution, and high costs . In our laboratory, a proficient feather-degrading strain of Bacillus licheniformis 8-4 was screened, which can fully degrade feathers within 48 h, yielding up to 2.62 g FKHPs per 10 g of feathers, with a conversion rate of 26.2% . Hence, it is a promising alternative to produce FKHPs via fermentation of B.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have demonstrated that feather keratin fermentation using Bacillus licheniformis 8− 4 yields feather keratin hydrolytic peptides with strong antioxidant activities in vitro. 17 Using ultrafiltration, HPLC purification, and LC/MS-MS identification, two novel peptides, CRPCGPTP (CP-8) and ANSCNEPCVR (AR-10), were isolated and exhibited significant antioxidant activity. Specifically, CP-8 exhibited IC 50 values of 0.92 and 0.033 mg/ mL for scavenging ABTS and DPPH radicals, respectively, while AR-10 showed IC 50 values of 0.84 and 0.034 mg/mL for eliminating ABTS and DPPH radicals, respectively.…”
Section: •−mentioning
confidence: 99%
“…In recent years, an increasing number of research teams have prepared bioactive peptides with antioxidant, antiaging, and antihypertensive properties from feather keratins through fermentation or composite enzymatic hydrolysis. However, most studies remain at preliminary stages without in-depth identification and mechanistic elucidation of the bioactive peptides. Our previous studies have demonstrated that feather keratin fermentation using Bacillus licheniformis 8–4 yields feather keratin hydrolytic peptides with strong antioxidant activities in vitro . Using ultrafiltration, HPLC purification, and LC/MS-MS identification, two novel peptides, CRPCGPTP (CP-8) and ANSCNEPCVR (AR-10), were isolated and exhibited significant antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%